Effect of Work Motivation on Employee Performance: Pengaruh Motivasi Kerja terhadap Kinerja Pegawai - Kelik Purwanto (International Journal of Management and Business (IJMB), 2020)
Research was conducted with to determine extentthe influence work motivation simultaneously on employee performance. How far the influence work motivation partially employee performance. This type research conclusive research that answering problem that requires solution using quantitative descriptive approach. Analysis Techniques with Validity Test, Instrument Reliability Test, Descriptive statistical analysis, Hypothesis Test, Linearity Test, Multiple Linear Regression Analysis.Motivation together has positive effect employee performance based the Summary model above that the coefficient R is (0.730) and the Adjusted R Square coefficient value 0.510 which means that there is influence of work motivation is (51%) and the rest (49%) in influenced other variables not examined To see whether work motivation has a positive and significant effect on employee performance, it can be seen that the value f_count 23.531 greater than f_table of 2.75, which 23.531> 2.75 with significance level of 0.000. Work motivation has positive and significant effect on employee performance seen in the coefficient table, value of 2.034 is greater than t_table 1.99897 with a significant level smaller than alpha (0.046 <0.05), then Ho is rejected and accepted Conclusion Motivation Variable (X_1) as independent variables in this study simultaneously and partially have a positive and significant effect on employee performance.